Development of a New Class of Thiocyanate-Free Cyclometalated Ruthenium(II) Complex for Sensitizing Nanocrystalline TiO2 Solar Cells. (4th May 2011) - Singh, Surya Prakash; Islam, Ashraful; Yanagida, Masatoshi; Han, Liyuan
Abstract : We designed and developed a new class of thiocyanate-free cyclometalated ruthenium sensitizers for sensitizing nanocrystalline TiO2 solar cells. This complex shows appreciably broad absorption range. Anchoring to nanocrystalline TiO2 films for light to electrical energy conversion in regenerative photoelectrochemical cells achieves efficient sensitization to TiO2 electrode. With this new sensitizer, there were a power conversion efficiency of 4.76%, a short-circuit photocurrent density of 11.21 mA/cm 2, an open-circuit voltage of 0.62 V, and a fill factor of 0.68 obtained under standard AM 1.5 sunlight.